2010
DOI: 10.1590/s1516-80342010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Adesão à terapia em motricidade orofacial no ambulatório de Fonoaudiologia do Hospital das Clínicas da Universidade Federal de Minas Gerais

Abstract: OBJETIVO: Caracterizar o atendimento em motricidade orofacial no Ambulatório de Fonoaudiologia do Hospital das Clínicas da Universidade Federal de Minas Gerais quanto à adesão e sucesso da terapia, bem como comparar dados dos pacientes que buscaram atendimento ativamente no Ambulatório de Fonoaudiologia e dos pacientes encaminhados pelo Ambulatório do Respirador Oral da mesma instituição. MÉTODOS: Foram investigados 90 prontuários de todos os pacientes em alta ou desligados, que buscaram tratamento pelos Ambul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Most research previously reviewed agrees on the findings of the present study, whereby there is higher incidence of referrals to speech therapy for males [6][7][8][9][10][11][12][13] . The explanations for this finding are not consensual, and an author states that the brains of boys have slower maturation than those of girls 6 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most research previously reviewed agrees on the findings of the present study, whereby there is higher incidence of referrals to speech therapy for males [6][7][8][9][10][11][12][13] . The explanations for this finding are not consensual, and an author states that the brains of boys have slower maturation than those of girls 6 .…”
Section: Discussionsupporting
confidence: 90%
“…It would be interesting to continue the record of the activities for conducting research with a wider range of records. Other studies have reported difficulty accessing data from medical records for the same reason [10][11][12][13][14][15][16] . There should be uniformity in medical records in institutions for more adequate records of the procedures, production and conduction of more reliable research.…”
Section: Discussionmentioning
confidence: 99%
“…The major reason (accounting for 70% of cases) was abandonment/failure on the part of the patients to show up for the sessions. A study conducted at a speech therapy clinic of the Federal University of Minas Gerais, at Belo Horizonte, MG, Brazil, also found excessive absences to be the main reason for discontinuing treatment 35 . Adherence to treatment is fundamental to therapeutic progress.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of it is a very common problem in medical practice 5 . Adherence to treatment can be considered when the patients and/or family members accept and follow the instructions, prohibitions and prescriptions of the professional responsible for treatment 6 . However, there are definitions that are broader and more conscious of the dynamics of the process that relate to the concept of active, voluntary and collaborative involvement of the patient in mutually acceptable behavior, with the aim of producing the desired therapeutic or preventive results 7 .…”
Section: Conflict Of Interest: Non-existentmentioning
confidence: 99%